Unpresidented : a biography of Donald Trump - Brockenbrough, Martha (Square Fish, 2020)
Provides an in-depth, heavily researched biography of Donald Trump, detailing his youth, ascension to inheriting a real estate empire, his unlikely political career, and his eventual election as forty-fifth president of the United States. Contains an extensive family tree and is punctuated throughout by quotes, tweets, and photographs.